How mobile do you go: a study of 5 news media start-up cases in Portugal - Crespo, Miguel (2020)
Journalistic start-ups are thriving around the world, bringing new approaches to the news media environment in terms of concepts, contents, dissemination, internal organization, business models and, of course, consumption patterns. But the concept of start-up, commonly used in the IT area (traditionally more agile in terms of innovation), is not easy to be adapted and redefined for the more traditional news media environment. All over the world, innovation is growing in the news media business, and start-ups are a big source for it, even if the inherent fragility of many projects don’t allow these new companies to fully accomplish all their objectives, even when they can assure its survival after the first years of activity. This research aims to create a prospective view on the evolution of the mobile performance and consumption of news. As a case study, we try to do a panorama on the mobile consumption and performance of news in the Portuguese journalistic start-up scene, looking at a diversity of projects, with different goals, business models and audiences - and the relations established between them.